Optimization and monitoring of solar power plant as a hybrid energy for tea leaf dryer based on SCADA system - Syahid, Syahid; Larasati, Pangestuningtyas Diah; Pramurti, Adeguna Ridlo; Muqorrobin, Mochamad; Riyadi, Aji Hari (Jurnal Polimesin, 2024)
Previous research has discussed tea drying machines with energy sources from PLN. Tea drying machines with refrigerant systems require large electrical energy costs. The electrical energy produced by a tea drying machine is proportional to its performance and cost. This research designed a 400 WP solar cell (PLTS) as a power supply for drying tea leaves. PLTS was combined with a PLN electricity source. Hybrid energy from PLTS and PLN was designed to maximize the use of electrical energy used by drying tea leaves. PLC and SCADA were used to monitor input current, output voltage, and output power. PLC and SCADA can optimize load requirements. When the solar radiation received by the solar panels was not optimal, PLN was able to back up load requirements. The average voltage produced by hybrid energy was 232.4 V. Hybrid energy was able to save power usage of 108.92 W or 12.8% of the load power requirements